Pencegahan Stanting Lembang Tondon Langi Kecamatan Tondon Kabupaten Toraja Utara - Permata Sari; Heppyanti Ponno; Gabryella Ivanka Rerungan; Helba Rundupadang; Intan Intan (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Community Service (PKM) which is located in Lembang Tondon Langi', Tondon District, North Toraja Regency is one of the places where we served for approximately one and a half months. In the work program that we are implementing, the focus is more on preventing stunting that occurs in Lembang Tondon Langi'. Where this work program is one of the themes that has been determined by the campus, namely